Preparation of gamma-Fe2O3 nanoparticles using DC thermal arc-plasma route, their characterization and magnetic properties - Banerjee, Indrani; Khollam, Y. B.; Balasubramanian, C.; Pasricha, R.; Bakare, P. P.; Patil, K. R.; Das, A. K.; Bhoraskar, S. V. (Scripta Materialia, 2006)
gamma-Fe2O3 particles were prepared, for the first time, using a direct current thermal arc-plasma route. The powder was characterized using X-ray diffraction, Mossbauer spectroscopy, X-ray photoelectron spectroscopy, chemical analysis, vibrating sample magnetometry C and transmission electron microscopy. The high purity, stoichiometry and spherical morphology of the gamma-Fe2O3 particles (saturation magnetization = 79 emu g(-1) and coercivity = 348 Oe) were confirmed. (c) 2006 Acta Materialia Inc. Published by Elsevier Ltd. All rights reserved.
Keywords: chemical analysis; DC thermal arc-plasma route; maghemite; Mossbauer spectroscopy; XPS

Photocatalytic activity and characterization of sol-gel-derived Cr(III)-doped TiO(2)-coated active carbon composites - Gambhire, A. B.; Lande, Machhindra K.; Mandale, A. B.; Patil, K. R.; Arbad, B. R. (Philosophical Magazine, 2008)
Cr(III)-doped, TiO(2)-coated active carbon (Cr-TiO(2)/AC) were prepared by a sol-gel method. The effect of supports, including TiO(2) and active carbon (AC), on the molecular structure and photocatalytic activity of chromium oxide for complete decomposition of EDTA has been examined with respect to the content of Cr on the catalyst surface. The photocatalytic activity of the Cr-TiO(2)/AC composites was evaluated in the decomposition of EDTA solution under UV irradiation. The results indicate that Cr-TiO(2)/AC has a higher efficiency in decomposition of EDTA than TiO(2), TiO(2)/AC or active carbon. This was attributed to the different functions of active carbon and chromate species. (1) Nanosize TiO(2) particles on composites were not reunited, possible because active carbon retards transformation of anatase into rutile and decreases the crystallite size. (2) Production of high concentrations of organic compound near Cr-TiO(2). (3) Carbon in active carbon causes some of the TiO(2) to reduce to Ti(3+) ions, which prevents electron-hole pair recombination. (4) Formation of polychromate species, with a stronger redox capability, on the surface of TiO(2)/AC. It was found that the addition of Cr to TiO(2) sol could suppress the grain growth of TiO(2) crystals and increase the hydroxyl content on the surface of TiO(2)/AC. The photocatalytic efficiency and activity of the composites remained good, even after three cycles.
Keywords: EDTA; photoactive; sol-gel; Titanium dioxide; XPS

Synthesis and characterization of high-surface-area Ag2O-doped SnO2 nanomaterial - Gambhire, A. B.; Lande, Machhindra K.; Kalokhe, S. B.; Shirsat, M. D.; Patil, K. R.; Gholap, Ramkrishna S.; Arbad, B. R. (Philosophical Magazine Letters, 2009)
Nanosized tin dioxide-based powders containing silver and palladium oxides have been prepared by coprecipitation reaction. XRD, TEM, and XPS analysis were carried out for investigation of crystalline structure and surface morphology. The best reactive conditions were determined, such as the concentration of the reactants, pH value, surfactants, reaction temperature, and time. The material obtained is nanocrystalline, having a particle size in the range of 5.21-7.42 nm. Effect of doped-Ag2O on the crystal size of the nanoparticles and the influence of the presence of a second dopant (Pd) on the Ag2O/SnO2 matrix was discussed.
Keywords: Ag2O:SnO2; Nanomaterials; XPS

Investigations of CdS and Ag-CdS nanoparticles by X-ray photoelectron spectroscopy - Thakur, Priya; Joshi, Satyawati S.; Patil, K. R. (Applied Surface Science, 2010)
In the present report, CdS and Ag-CdS nanoparticles were synthesized using cysteine as a capping agent. Surface properties CdS and Ag-CdS nanoparticles were studied by X-ray photoelectron spectroscopy (XPS). XPS study of CdS nanoparticles was carried out as a function of pH and for a refluxed sample at pH 11.2. Effect of dopant concentration on surface properties of Ag-CdS nanoparticles was also studied for as prepared samples as well as for annealed sample at 2% doping. Effect of pH, dopant concentration, and effect of particle size on different sulfur species present in the system was studied. Features of Cd 3d, S 2p and Ag 3d core level have been discussed in detail. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: Ag-CdS; CdS; Cysteine; XPS

Characterization of surface acid sites in tin-silicalite-1 (Sn-MFI) molecular sieve by X-ray photoelectron spectroscopy - Niphadkar, P. S.; Patil, K. R.; Joshi, P. N. (Microporous and Mesoporous Materials, 2011)
The nature, strength and density of surface acid sites in Sn-MFI molecular sieves with different Sn-content were characterized by N 1s high resolution photoelectron peak of chemisorbed pyridine in combination with pyridine-IR and TPAD. Two peaks emerged at 399.5 +/- 0.2 and 401.5 +/- 0.2 eV by deconvoluting composite N is peak were assigned to chemisorbed pyridine on weak and relatively strong Lewis acid sites, respectively. The relative percentage of strong Lewis acid sites was found to increase with the decrease of framework Sn content. A close agreement was observed between the ratios of weak Lewis acid sites to strong Lewis acid sites obtained from XPS and TPAD. (C) 2010 Elsevier Inc. All rights reserved.
Keywords: Lewis acidity; Pyridine chemisorption; SiO2/SnO2 molar ratio; Sn-MFI; XPS

Surface characterization of Au-ZnO nanowire films - Jamali-Sheini, Farid; Yousefi, Ramin; Patil, K. R. (Ceramics International, 2012)
Au-ZnO nanowire films have been synthesized by annealing Zn foils coated with a thin layer of gold. An X-ray diffraction study found that the synthesized ZnO consists mainly of a hexagonal wurtzite structure along with a small amount of AuZn3 phase. Scanning electron images showed that the ZnO wires extend to several microns in length. X-ray photoelectron spectroscopy studies confirmed the oxidation states of Au and Zn. An asymmetric O ls peak indicates the presence of oxygen in an oxide layer and O H groups on the films surfaces. Photoluminescence (PL) spectra showed different visible peaks for pre-annealed films, while for annealed films an UV peak appeared. In addition, the PL analysis showed that the overall intensity of photoluminescence decreased significantly after the films were annealed. Raman spectroscopy results also indicated that the crystalline quality of the films improved with annealing. This could be attributed to a decrease in oxygen vacancies and/or absorption of O-H groups on the surface of ZnO film. The highly hydrophilic surface with a water contact angle of similar to 155 degrees was obtained after annealing in air. (c) 2012 Elsevier Ltd and Techna Group S.r.l. All rights reserved.
Keywords: Au-ZnO; Highly hydrophilic; Nanowires; XPS